Essays and addresses toward a liberal education - Baird, Albert Craig 1883- (Ginn and company, 1934)
"The present anthology ... attempts to set forth significant point of view in various fields of thinking - educational, philosophical, aesthetic, moral and religious, political, national and international, economic and social."--Introductory note.